2017
DOI: 10.1007/s13346-017-0380-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assay for measuring real time topotecan release from liposomes: release kinetics and cellular internalization

Abstract: Topotecan is a drug that is under investigation for the treatment of neuroblastoma and has been encapsulated into liposomes to improve its therapeutic efficacy. However, liposomal formulations still need to be optimized for drug retention and new techniques to measure drug release are required to better understand this process. Here, a novel in vitro method based on fluorescence de-quenching and an automated microscopy imaging platform were developed for monitoring, in real time, the release of topotecan from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We would like to underline that ICG fluorescence intensity of the DOX@GdMSNs-ICG-TSLs + NIR group was the strongest compared to free the ICG + NIR and DOX@GdMSNs-ICG-TSLs group. Combined with flow cytometry data in Figure S5, it demonstrated that DOX@GdMSNs-ICG-TSLs were easier to achieve cell internalization under the assistance of lipid bilayer and NIR irradiation. …”
Section: Results and Discussionmentioning
confidence: 80%
“…We would like to underline that ICG fluorescence intensity of the DOX@GdMSNs-ICG-TSLs + NIR group was the strongest compared to free the ICG + NIR and DOX@GdMSNs-ICG-TSLs group. Combined with flow cytometry data in Figure S5, it demonstrated that DOX@GdMSNs-ICG-TSLs were easier to achieve cell internalization under the assistance of lipid bilayer and NIR irradiation. …”
Section: Results and Discussionmentioning
confidence: 80%
“…This phenomenon may be attributed to the liposomes present of endocytosis advantage. 21,22 Besides, when the liposomes enter into HCT-116 cells, sustained intracellular release of Rapa also lead to a raised intracellular concentration of Rapa. 23…”
Section: Dovepressmentioning
confidence: 99%
“…Topotecan undergoes a pH-dependent, reversible hydrolysis into a nonactive carboxylate at physiologic pH (Devriese et al, 2015). With this in mind, a liposomal topotecan formulation was prepared to protect the cytostatic drug from this pH-induced hydrolysis (Chernov et al, 2017;Gilabert-Oriol et al, 2017). Pharmacokinetic studies showed that the nanoformulation exhibited a 10-fold increase in plasma half-life values in comparison with equivalent doses of topotecan (Hycamtin); however, encapsulated topotecan only modestly increased the life span of NB mice.…”
Section: Nontargeted Nanomedicines For Neuroblastomamentioning
confidence: 99%